2010
DOI: 10.1136/bjo.2009.178327
|View full text |Cite
|
Sign up to set email alerts
|

Selective retina therapy for acute central serous chorioretinopathy

Abstract: NCT00987077.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 20 publications
3
63
2
3
Order By: Relevance
“…However, all of them were conducted by the same group. A first case series in 2006, comprising 5 patients, showed promising preliminary results in terms of subretinal fluid regression with coexistent PED without any cases of RPE rips [115]. In the same year, another study with 27 patients could also show a very high subretinal fluid regression rate.…”
Section: Treatmentmentioning
confidence: 83%
See 2 more Smart Citations
“…However, all of them were conducted by the same group. A first case series in 2006, comprising 5 patients, showed promising preliminary results in terms of subretinal fluid regression with coexistent PED without any cases of RPE rips [115]. In the same year, another study with 27 patients could also show a very high subretinal fluid regression rate.…”
Section: Treatmentmentioning
confidence: 83%
“…This selective treatment of the RPE is meant to trigger the regeneration of the RPE and a long-term metabolic increase at the chorioretinal junction [116]. Three different studies and case series have been carried out to evaluate the effect of SRT in the setting of CSC [115,117,118]. However, all of them were conducted by the same group.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Subthreshold micropulse diode laser treatment is applied in an attempt to trigger the regeneration of the RPE and a long-term metabolic increase at the chorioretinal junction, 36 which may increase SRF resorption by the RPE. 37 Micropulse laser treatment is not thought to affect the choriocapillaris directly. The lack of effects on choriocapillary flow in patients after micropulse laser treatment is therefore not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized prospective study of 30 patients with chronic central serous chorioretinopathy of at least 3 months' duration with 14 eyes randomized to SRT and 16 eyes as controls found a statistically significant improvement in mean visual acuity with 12.7 letters gained in the laser group versus 6.3 letters gained in the control group (p=0.04). SRT also resulted in less subretinal fluid with a decrease of 203 microns in retinal thickness with laser versus 41 microns in control patients at 3 months (p=0.005) [47] . A prospective uncontrolled study of 39 patients with diabetic macular edema found an improvement of 2.4 letters of vision 6 months after laser application (p=0.02).…”
Section: Paulus Ym Retinal Lasersmentioning
confidence: 93%